Ionization Coefficients and Breakdown Potential in Krypton - Mat Yunus, W. Mahmood (1986)
Ionization currents in research grade krypton between plane parallel gold-plated electrodes at separation up to 3 cm were measured in the range of 14 < E/P -:(" 200 volt cm - 1 torr -1 and 2 < p.-:(" 130 torr where E is the applied electric field and p ** is the gas pressure. The values of ionization coeffidents of/P deduced from these measurements were lower than the values obtained by Kruith of(1940) but higher than the values obtained by Dutton et al. (1983), in the range of E/P < 200 volt cm -1 torr -1. Within the limit of experimental error, /P was found to be a function of E/P only. The measured values of breakdown potentials were in good agreement with the values calculated from the breakdown criterion and satisfied the similarity principle.